210 Antibody function, antigenic target and glycans determine the transfer of herpes simplex virus (HSV) antibodies (Abs) from mothers to newborns and transfer is altered by SARS-CoV-2. (April 2022) - Mahant Mahant, Aakash; Estrada Trejo, Fatima A.; Aguilan, Jennifer T; Sidoli, Simone; Herold, Betsy C.
Abstract : OBJECTIVES/GOALS: Murine and clinical data suggest that antibody-dependent cellular cytotoxicity (ADCC) is associated with greater protection against disseminated neonatal HSV disease. To quantify the relative transfer of Abs with different functions and targets, we conducted a prospective study of mother-infant term and preterm dyads pre and during COVID-19 METHODS/STUDY POPULATION: Total and HSV lysate, glycoprotein D (gD) and glycoprotein B (gB)-specific IgG, IgG1 and IgG3 as well as HSV neutralizing Abs (nAbs) and ADCC were quantified in paired 3rd-trimester pregnant women and their newborns (cord) blood. Transfer ratios (TR) were defined as cord:maternal Ab levels. IgG1 and IgG3 subclass and gD or gB-specific Abs were isolated by column purification and glycan profiles were assessed by mass spectrometry. The study population included 21 term and 15 preterm dyads who were HSV-1 (+/- HSV-2) seropositive enrolled between 2018-2019 (pre-COVID) and 25 additional HSV-1 (+/- HSV-2) seropositive term dyads whose mothers were SARS-CoV-2 PCR and COVID Ab+ at delivery; 14 were asymptomatic and 11 had mild-moderate COVID disease. None of the mothers had active genital HSV lesions during delivery RESULTS/ANTICIPATED RESULTS: Anti-HSV IgG, IgG1 and IgG3 TR were higher in term vs. preterm dyads (p<0.05). The nAb TR was 2.4 in term vs. 0.8 in preterm (p<0.001) but the ADCC TR was < 1.0 for both. To determine if the latter reflected antigenic target, subclass or glycans, we enriched for gD and gB specific and IgG1 and IgG3 Abs. The gD Abs were IgG1 and had only neutralizing activity. In contrast, gB Abs were polyfunctional and included IgG1 and IgG3 but only the IgG1 Abs had ADCC activity. The gD Abs were enriched for glycans associated with an affinity for the neonatal Fc receptor (FcRn); gB Abs expressed glycans associated with both FcRn and FcÎ³RIIIa binding. There was no significant difference in total HSV-specific IgG TR in pre-COVID vs post-COVID dyads but the nAb TR was lower (p=0.018) and ADCC TR higher (p<0.001) in the COVID compared to pre-COVID cohort DISCUSSION/SIGNIFICANCE: HSV ADCC Abs, which may provide greater protection than nAbs against neonatal disease, transfer poorly particularly to preterm newborns. However, in the setting of SARS-CoV-2, the TR of HSV ADCC is significantly higher. This may reflect alterations in the placental architecture and/or glycan composition which is currently being investigated.